1996
DOI: 10.1021/bi961462l
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Role of Arg 110 of Murine Leukemia Virus Reverse Transcriptase in the Catalytic Mechanism:  Biochemical Characterization of Its Mutant Enzymes

Abstract: Based on the projected three-dimensional equivalence of conserved amino acids in the catalytic domains of DNA polymerases, we propose Arg 110 of MuLV RT to be an important participant in the catalytic mechanism of MuLV RT. In order to obtain evidence to support this proposition and to assess the functional importance of Arg 110, we carried out site directed mutagenesis of Arg 110 and replaced it with Lys, Ala, and Glu. The mutant enzymes were characterized with respect to their kinetic parameters, ability to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
58
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 37 publications
5
58
0
Order By: Relevance
“…The studied enzymes included K103A, R110A, D114N, R116K, D114N/R116K, R116L, and N119A, all of which failed to support replication or led to a delayed phenotype when tested in viruses in the experiments described here. As previously reported, K103A and R110A enzymes retain less than 10% of wild-type activity (2,3), while the remaining enzymes retain 40 to 70% of wild-type activity in the polyriboadenylate-oligodeoxyribosylthymine assay. However, despite their relatively high levels of activity on homopolymeric templates, all of the enzymes with substitutions for D114, R116, or N119 synthesized significantly less full-length product than the wild-type enzyme when assayed on an mRNA template, suggesting that they have processivity defects (25).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The studied enzymes included K103A, R110A, D114N, R116K, D114N/R116K, R116L, and N119A, all of which failed to support replication or led to a delayed phenotype when tested in viruses in the experiments described here. As previously reported, K103A and R110A enzymes retain less than 10% of wild-type activity (2,3), while the remaining enzymes retain 40 to 70% of wild-type activity in the polyriboadenylate-oligodeoxyribosylthymine assay. However, despite their relatively high levels of activity on homopolymeric templates, all of the enzymes with substitutions for D114, R116, or N119 synthesized significantly less full-length product than the wild-type enzyme when assayed on an mRNA template, suggesting that they have processivity defects (25).…”
Section: Discussionsupporting
confidence: 76%
“…K103, R110, D114, R116, and N119 are highly conserved. Predictions suggest that K103 and R110 form hydrogen bonds with the incoming nucleotide (2,3,18,25). D114, R116, and N119 are involved in critical interactions of the primer-template with the fingers domain in crystal structures of the N-terminal fragment of MLV RT complexed with DNA.…”
Section: Discussionmentioning
confidence: 99%
“…These include residues of the Tyr-X-Asp-Asp (YXDD) motif, the deoxyribonucleoside triphosphate (dNTP) binding site, the ␣-helix H of the thumb domain, the conserved Leu-Pro-Gln-Gly (LPQG) motif, the finger domain, and specific amino acids such as E89 and F160 in human immunodeficiency virus type 1 (HIV-1) RT (1, 3, 4, 10, 13, 16-18, 29, 35, 42, 50). The mechanism by which fidelity is maintained may encompass features in RT that involve the local geometry of the active site, the proper positioning of the template-primer complex, or the global effects attributed to different conformational states of the protein (8,18).It was previously shown that residues 110 to 116 in HIV-1 RT are located in the active site of RT and have a moderate to high solvent accessibility, suggesting that they may play a role in dNTP binding (22,44). Furthermore, extensive mutational analysis of residues Y115 and Q151 in HIV-1 RT revealed that substitution mutations at these sites could have drastic effects on substrate dNTP binding (35, 42) as well as resistance to nucleoside analogs (21,46).…”
mentioning
confidence: 99%
“…The catalytic importance of arginine has been shown in nucleotide substrate binding (29), and it may form a catalytic triad with serine and asparagine (30). Arginine can also have structural importance, as demonstrated by its role in conformational changes in murine leukemia virus reverse transcriptase (31). Evidence supporting a putative role for arginines and histidines in the ATP sulfurylase/APS kinase reaction mechanism comes from studies of both yeast and fungal ATP sulfurylases, which are inactivated by phenylglyoxal, which modifies arginines, and by diethylpyrocarbonate, which targets histidines (32).…”
mentioning
confidence: 99%